Lip color affects ERP components in temporal face perception processing - Hideaki Tanaka (Journal of Integrative Neuroscience, 2021)
This brief report investigates the relationship between the lip color of women’s faces and the latency and amplitude of the P1, N170, and early posterior negativity of event-related potential components. To show different color lipsticks affect face perception processing, we used EEG to observe these event-related potential components in 19 participants exposed to visual stimuli under four conditions: red lips, yellow lips, blue lips, and no-makeup. The results indicate a significantly higher attractiveness score for red lips than the other three conditions and a significantly shorter P1 peak latency for red lips than blue lips or no-makeup. This may reflect that red lips attract attention more than blue or natural lips in the early stages of face processing. The results indicate that the peak of early posterior negativity for red lips occurred significantly longer than for yellow lips, blue lips, or no-makeup. Early posterior negativity amplitudes were significantly larger to red lips than blue lips or no-makeup. These results may indicate that, at later stages of face processing, the high attractiveness of red lips is associated with slower and careful processing. In contrast, blue lips, which have a low attractiveness score, are processed speedily and carelessly. These present results suggest a novel possibility that P1 and early posterior negativity can be used as a biomarker for temporal face perception processing of facial attractiveness in the human brain.